The Prospects Of Daytime Running Lights For Reducing Vehicle Crashes In The U.S. - Williams, A F; Lancaster, K A
Daytime running lights increase visual contrast between vehicles and their background, improving their noticeability and detectability. Seven countries require motor vehicles to have lights on during all daytime periods--Canada, Denmark, Finland, Hungary, Iceland, Norway, and Sweden. Studies from these and other countries have generally indicated that daytime running lights use is associated with small to moderate reductions in multiple-vehicle daytime crashes, especially those involving vehicles approaching from the front or side. There is evidence also that initial positive effects of daytime running lights do not dissipate over time, that is, there is little support for novelty or habituation effects. The bulk of the evidence suggests that running lights do not lead to increases in collisions involving pedestrians and pedalcyclists, allaying concerns that there would be negative consequences of making these road users relatively less conspicuous. Most of the studies have been conducted in countries located at latitudes that are to the north of most of the continental U.S. and that have longer twilight periods and generally lower ambient illumination. The concern has been expressed that running lights may lose their effectiveness in countries located at lower latitudes, such as the U.S., because the lights will provide less of a contrast. General Motors Corporation and some other manufacturers are now providing running lights on new models with higher intensities than are used in Scandinavian countries. Findings in running lights studies suggest that their effect in the U.S. will be positive, and their introduction provides an opportunity to determine the effect. The costs of running lights are low, so even modest crash reductions would be cost effective.